Implementasi Sistem Rekomendasi Menggunakan Metode Collaborative Filtering Pada Aplikasi Pemesanan Menu Restoran Berbasis Android - Soleh, Muhamad; Ristianto, Bagas Eka (LPPM, 2025)
During the outbreak of the Corona virus disease (Covid-19), many changes have been experienced by society in various fields, including social, economic, political, and education. This has resulted in changes in people's daily activities, with many restrictions imposed to reduce the spread of the Covid-19 virus. These changes have also affected the food and beverage industry, which now uses mobile or web applications to serve customers. With the changes experienced by businesses that already use mobile or web applications, application or web development can be used to improve business by promoting the available menu at a food and beverage business by recommending the menu to customers through the application or web. The recommendation system is very influential for customers in making the decision to order other menus. The development of an application for menu recommendations using User-Based Collaborative Filtering with cosine similarity as the calculation of similarity value and prediction value calculation. The result of this research is an Android-based mobile application for ordering menu to be eaten in a restaurant, by providing a menu recommendation based on the prediction results conducted using the user-based collaborative filtering method.